The Effectiveness of Using Video Clip in Teaching English Vocabulary at SD Fastabiqul Khairat Samarinda - Erliana, Utari; Arbain, Arbain (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2020)
This study examines the effectiveness of video clip in teaching vocabulary to elementary school students. The researcher used a quantitative approach Âof one-group pre-test post-test design or single-subject experimental design. This research was conducted at SD Fastabiqul Khairat Samarinda at Utsman Bin Affan class of two grades consist of 25 students. The researcher was collected the data for three meetings, the researcher gave pre-test, treatment, and post-test in every meeting. The data were analyzed by using SPSS version 23 with an analysis of the Paired Sample T-Test to know the significant effect of using video clips in teaching English vocabulary. The result of this study showed that there was a significant effect of using video clips in teaching English vocabulary for three meetings. The significant (2-tailed) score of pre-test and post-test for three meetings was less than 0.05. The researcher concluded that using video clips in teaching English vocabulary to Utsman Bin Affan class was effective.